Evaluation of the Efficacy of Aprepitant on the Prevention of Chemotherapy-Induced Nausea and Vomiting and Quality of Life with Functional Living Index Emesis - Görkem Aksu; Doğu Canoğlu; İlhan Dolaşık; Fatih Ensaroğlu; Selçuk Y. Şener; Faden H. Aydın; Süleyman Temiz; Kazım Uygun (Balkan Medical Journal, 2013)
Objective: Functional Living Index Emesis (FLIE) is developed to evaluate the relationship between emesis and it's effects on patient's daily life and is far more relevant to detect the effectiveness of antiemetic treatment compared with self-diary reports. In this study, the efficacy of oral neurokinin-1 antagonist aprepitant on the prevention of chemotherapy-induced nausea and vomiting and quality of life is evaluated with FLIE.